PENGGUNAAN TRAKTOR PERTANIAN UNTUK PENGOLAHAN TANAH DALAM PEMBANGUNAN HTI - Dulsalam Dulsalam (Jurnal Penelitian Hasil Hutan, 1992)
A study on the use of farming tractor for  land tillage in timber estate  establishment was conducted at timber  estate area of  PT Barito Pacific Group in  South Sumatra  in 1991. The  objective  was to obtain technical and economic data on land tillage in timber estate using farming  tractor.  For this purpose, data on productivity, specification,  fixed cost and operating cost of ford farming tractor were collected. the  resuits were as follows   :1.    Land tiliage comprized three  activities namely.first plowing. second  plowing and harrowing.2.    Productiitrity in the first plowing ranged between 0.2184 ha/hour and 0. 3048 ha/hour with an average of 0. 2601 ha/hour.3.   Operation costs  in the first plowing varied from  63.206.  -/ha to Rp. 85,027.-/ha  with an average of   Rp. 71, 782.-/ha.4.   Productivity in the second plowing ranged between 0.2100  ha/hour and 0. 3240 ha/hour with an average of 0.2703 ha/hour5.    Operation COSIS in the second plowing varied from Rp. 57.315.,-/ha  to Rp. 88,428,-/ha  withan average of Rp.   69,583.-/ha.6.    Tractor productivity  in harrowing ranged between 0.3818 ha/hour and 0.5593  ha/hour with an average of 0.4702  ha/hour.7.    Costs for harrowing  varied from  Rp. 34,250.-/ha to Rp. 49,581,-/hq  with an average of Rp.  40,647.-/ha8.   Average cost of land  tillage using ford farming tractor was Rp. 182,012.-/ha.9.   it is suggested that soil condition in land tillage be considered to  save cost and power.